Yarn on yarn abrasion performance of high modulus polyethylene fiber improved by graphene/polyurethane composites coating. (January 2021) - Ning, Fanggang; He, Guifang; Sheng, Chunfu; He, Hongwei; Wang, Jian; Zhou, Rong; Ning, Xin
As a high-performance fiber, high modulus polyethylene fiber (HMPE) has been widely used in the rope industry. However, due to its low melting point and poor thermal conductivity, it tends to break under the conditions of repeated yarn on yarn abrasion during tension-tension fatigue or tension-bending fatigue. This paper puts forward a method to improve the yarn on yarn abrasion performance of HMPE using a functional graphene/polyurethane composites coating (FG/PU) and discussed the influence of yarn tension, abrasion frequency on the yarn on yarn performance. Based on the yarn morphology and abrasion temperature observation, the failure mechanism was discussed. The experimental results show that the FG/PU coating obtained can improve the yarn on yarn abrasion performance obviously, especially in the case of high-frequency and large tension condition.